Manufacturing of a portable electrospinning gun for biomedical applications - EKREN, NAZMİ (My University, 2022)
Electrospun patches have attracted interest in different biomedical fields, including tissue engineering and drug delivery. Portable electrospinning guns promise faster and more practical interventions in these areas. In this article, the design, construction and testing of a portable electrospinning gun are described to produce fiber and particle products. Results were discussed depending on the electrospinning gun\"s working system and properties of the products. The electrospinning gun system could have a high voltage of up to 30 kV. Also, no heating problems were encountered during high voltage values. Due to the uniformity, reproducibility and tunability of the produced PCL and PMSQ fibers, it can be said that electrospinning gun can be used in nanotechnology, drug delivery systems and wound dressing applications.
Keywords: İnşaat Mühendisliği; Yapı; Mühendislik ve Teknoloji; Civil Engineering; Structure; Engineering and Technology; İNŞAAT VE YAPI TEKNOLOJİSİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Malzeme Bilimi; CONSTRUCTION & BUILDING TECHNOLOGY; ENGINEERING; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE, MULTIDISCIPLINARY; MATERIALS SCIENCE; Metaller ve Alaşımlar; Malzeme Kimyası; Genel Malzeme Bilimi; Genel Mühendislik; Yapı ve inşaat; Mühendislik (çeşitli); Fizik Bilimleri; Metals and Alloys; Materials Chemistry; General Materials Science; General Engineering; Building and Construction; Engineering (miscellaneous); Physical Sciences; Electrospinning; electrospinning gun; fiber; wound dressing; biomedical; NANOFIBERS; JET; Electrospinning; electrospinning gun; fiber; wound dressing; biomedical